The Effectiveness of Outdoor Education on Student Creativity - Yogi Akin; Ryan Abu Bakar (JUARA : Jurnal Olahraga, 2023)
This study aims to determine the effect of outdoor education activities on student creativity. The method used in this study is an experimental method with a static group comparison design. The sample in this study were PGSD Physical Education students using a purposive sampling technique, totalling 40 students, namely 20 students who did outdoor education activities and 20 students who did not do outdoor education activities. The research instrument was a creativity questionnaire which was analyzed with the statistical technique of the Two-Average Equivalence Test with the treatment of outdoor education activities given six days in 2 weeks. Based on the data analysis, the hypothesis is accepted, which means that outdoor education activities have a significant effect on student creativity. This study concludes that outdoor education activities have a significant positive impact on student creativity. Outdoor education activities can be a good alternative in learning to increase creativity and other cognitive components.